2014
DOI: 10.1161/circheartfailure.113.000568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atrial Fibrillation on Exercise Capacity in Heart Failure With Preserved Ejection Fraction

Abstract: Background Atrial fibrillation (AF) is common among patients with heart failure and preserved ejection fraction (HFpEF) but its clinical profile and impact on exercise capacity remains unclear. RELAX was a multicenter randomized trial testing the impact of sildenafil on peak VO2 in stable outpatients with chronic HFpEF. We sought to compare clinical features and exercise capacity among HFpEF patients who were in sinus rhythm (SR) or AF. Methods and Results RELAX enrolled 216 HFpEF patients with 79 (37%) in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
90
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(105 citation statements)
references
References 51 publications
10
90
0
5
Order By: Relevance
“…Most prior studies have shown that patients with AF have a higher peak HR, which is likely a result of activation of sympathetic compensatory mechanisms to low cardiac output 8, 9, 17. In contrast, only 1 study showed that peak HR was not different between AF and non‐AF in patients with HFpEF,25 similar to our study, suggesting that the implementation of a strict rate control strategy in these patients may inhibit the essential normal compensatory response required to maintain adequate perfusion at peak exercise.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Most prior studies have shown that patients with AF have a higher peak HR, which is likely a result of activation of sympathetic compensatory mechanisms to low cardiac output 8, 9, 17. In contrast, only 1 study showed that peak HR was not different between AF and non‐AF in patients with HFpEF,25 similar to our study, suggesting that the implementation of a strict rate control strategy in these patients may inhibit the essential normal compensatory response required to maintain adequate perfusion at peak exercise.…”
Section: Discussionmentioning
confidence: 95%
“…Each of these mechanisms is of particular importance at peak exercise when maximal contractile reserve is used. As such, AF has been associated with exercise intolerance in patients with lone AF and more notably in those with associated heart disease 9, 23, 24, 25. Some studies have shown that peak VO 2 , a surrogate of maximal aerobic capacity,12 is 10% to 20% lower in patients with HFrEF with AF 6, 8, 9, 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrosis is especially prevalent in atrial remodelling in patients with HFpEF 29. In the RELAX trial, HFpEF patients with AF (37%) had more advanced disease and a significantly reduced exercise capacitance, which might be also related to the development of tachy‐cardiomyopathy 53. Likewise, others reported that AF is independently associated with greater exertional intolerance, natriuretic peptide elevation, and left anterior descending artery remodelling in HFpEF 53, 54.…”
Section: Clinical Impact Of Atrial Remodelling and Relevance In Heartmentioning
confidence: 99%
“…In the RELAX trial, HFpEF patients with AF (37%) had more advanced disease and a significantly reduced exercise capacitance, which might be also related to the development of tachy‐cardiomyopathy 53. Likewise, others reported that AF is independently associated with greater exertional intolerance, natriuretic peptide elevation, and left anterior descending artery remodelling in HFpEF 53, 54. Vice versa, in Framingham Heart Study participants, pre‐existing AF tended to be more strongly associated with new‐onset HFpEF (hazard ratio 2.34) than did HFrEF (hazard ratio 1.32), highlighting the relevance of atrial function in HFpEF 55…”
Section: Clinical Impact Of Atrial Remodelling and Relevance In Heartmentioning
confidence: 99%